Transcriptomic resources for environmental risk assessment: a case study in the Venice lagoon. (February 2015) - Milan, M.; Pauletto, M.; Boffo, L.; Carrer, C.; Sorrentino, F.; Ferrari, G.; Pavan, L.; Patarnello, T.; Bargelloni, L.
Abstract: The development of new resources to evaluate the environmental status is becoming increasingly important representing a key challenge for ocean and coastal management. Recently, the employment of transcriptomics in aquatic toxicology has led to increasing initiatives proposing to integrate eco-toxicogenomics in the evaluation of marine ecosystem health. However, several technical issues need to be addressed before introducing genomics as a reliable tool in regulatory ecotoxicology. The Venice lagoon constitutes an excellent case, in which the assessment of environmental risks derived from the nearby industrial activities represents a crucial task. In this context, the potential role of genomics to assist environmental monitoring was investigated through the definition of reliable gene expression markers associated to chemical contamination in Manila clams, and their subsequent employment for the classification of Venice lagoon areas. Overall, the present study addresses key issues to evaluate the future outlooks of genomics in the environmental monitoring and risk assessment. Graphical abstract: Highlights: Growing need to develop new resources for the evaluation of the environmental status. Identification of gene expression markers associated to chemical contamination. Employment of genomics to evaluate the environmental status of Venice lagoon areas. Hurdles and future outlooks of genomic tools in environmental risk assessment. Abstract : Genomics in risk assessment of Venice lagoon.